Construction of Analytic Solution for Time-Fractional Boussinesq Equation Using Iterative Method - Fei Xu; Yixian Gao; Weipeng Zhang (Advances in Mathematical Physics)
This paper is aimed at constructing analytical solution for both linear and nonlinear time-fractional Boussinesq equations by an iterative method. By the iterative process, we can obtain the analytic solution of the fourth-order time-fractional Boussinesq equation in R, R2, and Rn, the sixth-order time-fractional Boussinesq equation, and the 2nth-order time-fractional Boussinesq equation in R. Through these examples, it shows that the method is simple and effective.